NEXUS BETWEEN POPULATION VARIABLES AND ECONOMIC GROWTH IN NIGERIA: DIRECTION OF CAUSALITY - Qosim, Fasoye; OMIMAKINDE, John Akintayo; OMIMAKINDE, Elizabeth Adeteju (International Journal of Research -GRANTHAALAYAH, 2022)
The study investigated the direction of causality between population variables and economic growth in Nigeria between 1986 and 2020 using VAR Granger Causality/Block Exogeneity Wald Tests. The results of the findings revealed the existence of feedback effects among economic growth, death rate, birth rate and secondary school enrollments. The results further showed that population growth and per capita GDP growth are completely independent and that higher population growth rate did not translate to higher economic growth in Nigeria. The study concluded that an average population growth rate in Nigeria was not seen as being productive as it did not translate to economic growth.